2020
DOI: 10.1080/14693062.2020.1724070
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy co-benefits: a review

Abstract: Concern over mitigation costs impedes the adoption of the climate policies needed to achieve agreed global warming targets. While costs are important to consider, so are benefits. However, the evidence for climate policy co-benefits, that is, the benefits in addition to avoided climate change costs, is commonly overlooked in policy-making. In many areas, the research is limited and not comprehensively synthesised. This article counters that problem and reviews 239 peer-reviewed articles, selected from 1,749 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 246 publications
(293 reference statements)
0
69
0
3
Order By: Relevance
“…An increasing number of studies provide solid evidence that there are substantial economic benefits of climate action in the short as well as long term. Climate mitigation has substantial co-benefits, here and now, in terms of local economic, environmental and health benefits (Karlsson et al, 2020; Rauner et al, 2020). Recent research insights show that economically ‘optimal’ abatement could very well be in line with the UN climate targets of limiting global warming to well below 2°C and to actively pursue a 1.5°C limit (Burke et al, 2018a; Glanemann et al, 2020; Hänsel et al, 2020).…”
Section: New Insightsmentioning
confidence: 99%
“…An increasing number of studies provide solid evidence that there are substantial economic benefits of climate action in the short as well as long term. Climate mitigation has substantial co-benefits, here and now, in terms of local economic, environmental and health benefits (Karlsson et al, 2020; Rauner et al, 2020). Recent research insights show that economically ‘optimal’ abatement could very well be in line with the UN climate targets of limiting global warming to well below 2°C and to actively pursue a 1.5°C limit (Burke et al, 2018a; Glanemann et al, 2020; Hänsel et al, 2020).…”
Section: New Insightsmentioning
confidence: 99%
“…New studies on co-benefits have consistently been published over the past 10 years [ 17 ], but most studies only identified the aspects of co-benefits and stated their importance, presented the physical type of indicators, assessed the spatial change in mortality, or classified the estimation methods for all types of physical indicators [ 9 , 16 , 18 , 19 ]. Karlsson et al [ 20 ] is one exception that cited various types of health co-benefits measured in USD arising from the reduction in NH 3 , SO x , NO x , PM, and NMVOC in different countries due to different GHG emissions reduction and mitigation mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Local framing refers to the emphasis of pressing local issues resulting from climate change as well as highlighting the potential cobenefits that climate change mitigation can entail in a local context and has been identified as a key component affecting the capacity for climate action among local governments (Ryan 2015). Due to the recent upsurge of local climate initiatives both in the EU (Kona et al 2018) and internationally (Gordon and Johnson 2017), and given the large amount of cobenefits that could be gained from climate action (Karlsson et al 2020), SEA can play a vital role to play in building local support both internally and externally in these processes. However, as local climate plans are only compulsory in four of the EU member countries according to Reckien et al (2018), and this study indicates that SEA seldom is conducted for voluntarily adopted plans, this raises concerns regarding the dichotomy between voluntary and statutory local energy and climate planning in an international context as well.…”
Section: Implications For Energy and Climate Planningmentioning
confidence: 99%